(untitled) (Eurasian Medical Research Periodical, 2024)
Modern views on energy metabolism in a living cell are presented, information is presented on the mechanisms of its implementation in normal conditions and in pathology. Methods for diagnosing disorders of intracellular energy are covered in detail, including assessment of the activity of mitochondrial enzymes in blood lymphocytes, the level of total and bound carnitine using photoelectrocolorimetry and liquid tandem chromatography-mass spectrometry methods. The main clinical manifestations of mitochondrial disorders are described: pathological manifestations of the muscular and central nervous systems, heart, other somatic organs, multisystemic lesions.